Kolaborasi Sekolah dan Komunitas dalam Mengoptimalisasikan Kemandirian Finansial Pendidikan di Era Disrupsi Sosial - Muhammad Ilzamul Khoir; Alda Novita Rahmatillah; Moch. Jauharul Maknun Al Ma’ie (Education Reserach Center, 2025)
This research focuses on an empirical analysis of the influence of school community collaboration on financial independence in education. The research is motivated by the urgency of building a participatory and inclusive educational ecosystem as a strategy to improve the quality of educational services. The method used is a quantitative approach using multiple regression analysis techniques and non-parametric Kendall's tau-b and Pearson correlations. The study population included educators, education personnel, and community leaders involved at MA Bustanul Ulum Bondowoso, with 60 respondents selected through stratified random sampling. The results indicate that both school collaboration and community involvement have a significant and positive relationship with financial independence in education, with correlation coefficients of 0.321 and 0.664, respectively. The implications of this research emphasize the importance of strengthening educational policies based on collaboration and community participation as key pillars in sustainably enhancing financial independence in education. This research also enriches the educational management literature by presenting a model of the relationships between relevant variables in the context of local educational institution development